2016
DOI: 10.1097/md.0000000000005326
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic diagnosis of urorectal septum malformation sequence and chromosomal microarray analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Our group has found that sonographic phenotypes are related to genotypes by using CMA. [ 15 19 ] Considering this, series of genetic analyses were performed in order. G-band karyotype analysis and FISH were performed to exclude aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has found that sonographic phenotypes are related to genotypes by using CMA. [ 15 19 ] Considering this, series of genetic analyses were performed in order. G-band karyotype analysis and FISH were performed to exclude aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…RBFOX1 is located in 16p13.3 near 16p13.2, a genomic region associated with several syndromes whose phenotypes include UDT, including alpha thalassemia/ mental retardation associated with chromosome 16 (ATR-16) (Gibson et al, 2008), 16p13.3 deletion or duplication, (Mattina et al, 2012;Rusconi et al, 2015), and the 16p13.2 deletion syndrome. Deletions within 16p13.3-13.2 or RBFOX1 were reported in three boys with different presentations of syndromic UDT (Ramanathan et al, 2010;Milone et al, 2016;Pei et al, 2016), in one case associated with an anogenital anomaly, and in a case of Müllerian aplasia (Sandbacka et al, 2013). Similarly, RBFOX1 duplication was reported in a female with cloaca and associated renal anomalies (Harrison et al, 2014), supporting a functional role for this gene in urogenital development.…”
Section: Discussionmentioning
confidence: 93%
“…Prenatal diagnosis by chromosomal microarray in a pregnancy suspected with URSMS detected paternally inherited 111.8Kb deletion at 16p13.3 in the affected fetus (Pei et al, 2016). Similarly, ZNF157, SP8, ACOT9, and TTLL11 are thought to be associated with VATER/ VACTERL following exome sequencing in a cohort of 21 families (Kolvenbach et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The latter deletion included a plausible candidate, hedgehog acyltransferase ( HHAT ); however, Sanger sequencing of independent patients with cloacal defects did not identify any significant variants in this gene. Prenatal diagnosis by chromosomal microarray in a pregnancy suspected with URSMS detected paternally inherited 111.8Kb deletion at 16p13.3 in the affected fetus ( Pei et al, 2016 ). Similarly, ZNF157, SP8, ACOT9 , and TTLL11 are thought to be associated with VATER/VACTERL following exome sequencing in a cohort of 21 families ( Kolvenbach et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%